CLINICAL EVALUATION OF SHASHILEKHA VATI IN THE MANAGEMENT OF SHVITRA WITH SPECIAL REFERENCE TO VITILIGO - Kavita, Patil; Sachin, Patil; Sagar, Narode; Ulhas, Durugkar (International Journal of Ayurveda and Pharma Research, 2015)
In Ayurveda, it is described that Viruddha aahar is the main etiological factor for so many diseases. Shvitra is one of them. This study focuses to develop evidence based support for efficacy of textual reference of Yogaratnakara regarding Shvitraghna property of Shashilekha Vati with Bakuchi tail and Madhu as Anupana with special reference to vitiligo. Shashilekha Vati was prepared according to the method mentioned in the classical text of Yogaratnakara. The trial was conducted on a sample size of 60 divided in two groups. In the criteria of assessment, measurement of area of lesion, nature of regimentation and degree of regimentation were taken. It is observed that there is significant regimentation in the treated lesion and reduction in total area of lesions.Shashilekha Vati with Anupana enters to all Sukshmastrotasas and it acts on dash, Dhatu by properties of Sukshma, Tikshna guna and Ushna virya. Thus it does Diana, patina and acts as Tayca, Varna. Oil of Bakunin acts on arterioles of sub capillary plexus due to which they dilate and increase the plasma in this area. At the same time copper acts on enzyme tyrosines. Due to which melanoblasts are stimulated. They further exude and diffuse into the decolourised area and pigmentation takes place in that area. It is observed that out of 30 patients in Drug Group i.e. taking Shashilekha Vati, 19 patients had marked to complete (76-100%) regimentation, 7 patients had marked (51-75%) regimentation, 3 patients had moderate (26-50%) regimentation and only one patient had minimal (below 25%) regimentation. The Drug in Group A-Shashilekha Vati showed significant regimentation and reduction in area of lesions as compared to Group B.